A Detail Analysis on AWT and ATT for Different CPU Scheduling Algorithms for Different Cases - Dr. Biswarup Samanta, Arinjay Biswas, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The sequence of execution of processes in multiprogramming plays a very crucial role to optimize the utilization of CPU. It has been found that CPU Scheduling algorithm serve as the basis of the multiprogramming. This paper presents the relationship between existing algorithms w.r.t A.W.T and A.T.A.T. through different cases. There are 5 cases where each case has 4 parts and each part represents different existing algorithms i.e. FCFS, SJF, RR, PB. Each part consists of 4 processes with different or same priority and arrival time depending upon the particular case, as designed in the section 4 of this paper. The goal of this paper is to find out the relationship w.r.t. A.W.T. and A.T.A.T., when different cases are implemented on the existing algorithms and find the fastest algorithm amongst the existing algorithms taken in this paper.